Effect of fenugreek seeds and Bacillus-based direct-fed microbials on the growth performance, blood biochemicals, and intestinal histomorphology of broiler chickens - Paneru, Deependra; Tellez-Isaias, Guillermo; Arreguin-Nava, Margarita A.; Romano, Nicholas; Bottje, Walter G.; Asiamah, Emmanuel; Abdel-Wareth, Ahmed A. A.; Lohakare, Jayant (Frontiers in Veterinary Science, 2023)
The objective of the present study was to evaluate the potential synergistic impact of the combination of fenugreek seeds (FS) and Bacillus-based direct-fed microbials (DFM) on growth performance, intestinal health, and hematological parameters of broiler chickens.A total of 160 one-day-old (Ross 308) broiler chicks were randomly assigned to a 2 ×x 2 factorial arrangement, with two levels of FS (0 and 5 g/kg) and two levels of Bacillus-DFM (0 and 0.1 g/kg), with five replicates of 8 birds each.The result showed that dietary supplementation of FS at 5 g/kg did not improve the growth performance of broilers but impaired the early growth performance by reducing body weight gain and increasing feed conversion ratio, which was recovered during finisher phase. Dietary supplementation of Bacillus-based DFM at 0.1 g/kg did not affect the performance variables but increased the feed conversion ratio. The interaction of fenugreek seeds and Bacillus-based DFM showed synergistic effects on growth performance during the later stages of production. However, antagonistic effects were observed on the blood parameters and the gut morphology.This study demonstrated that FS and DFM had different effects on the broiler health and production depending on the phase of production. The interaction between FS and DFM revealed synergistic effects on growth performance during the finisher phase, but antagonistic effects on blood parameters and gut morphology. Further studies are needed to elucidate the underlying mechanisms and optimize the dosage and combination of FS and DFM for broiler health and production.